The Mediator Role of Workplace Spirituality in The Relationship Between Psychological Capital and Entrepreneurial Behavior: Field Research in the center of the Iraqi Ministry of Oil - صبر رنا ناصر (Journal of Economics and Administrative Sciences, 2018)
Abstract The research aims to identify the mediator role of workplace spirituality in the relationship between psychological capital and entrepreneurial behavior: field research to a sample opinions from employees at the center of the Iraqi ministry of Oil . The importance of the current research emerged from paucity of studies that have attempted to identify and know the nature of the relationship between the variables as well as trying to find the current address and realistic problem directly affects the performance of employees in the Iraqi oil sector. In order to achieve the goal of research the use of the analytical method (quantitative) was relying on the questionnaire as an essential tool for collecting research data Has been chosen center of the Iraqi Ministry of Oil a field to search, included (307) Employees At all administrative levels in the Ministry. The evaluating and testing the Validity and Reliability of the measurement research tools we have been relying on test coefficient (Cronbach’s alpha) as well as on the use of confirmatory factor analysis for variables research. Then we conducted data analysis and test hypotheses using appropriate statistical tools (some of descriptive statistics, Correlation analysis, direct and indirect effect analysis using the structural equation modeling method, and the Sobel test to verify the significance of the intermediate role assumptions. The results showed correctness or validity of all the research hypotheses, Accordingly, a set of conclusions was formulated, the most important of which is that variable of the workplace spirituality partially mediates the relationship between psychological capital and entrepreneurial behavior, The research concluded with a number of recommendations Which ensures a range of administrative mechanisms and practices that promote the building of psychological capital and create an environment conducive to the development of workplace spirituality and entrepreneurial behavior of employees.